KEANEKARAGAMAN PTERIDOPHYTA DI KAWASAN TAMAN NASIONAL MATALAWA DI PULAU SUMBA - Yunita Suhartini Milla; Erfy Melany Lalupanda; Anita Tamu Ina (Jurnal Penelitian Kehutanan BONITA, 2021)
The diversity of ferns (Pteridophyta) in the Matalawa National Park (TN) is beginning to be disturbed. This situation is caused by the activities of humans living in the vicinity of the Matalawa National Park who use the forest in an unsustainable way. The purpose of this study was to describe the diversity of Pteridophyta in the Matalawa National Park on the island. The results showed that there were 22 types of Pteridophyta at all research stations. The diversity of Pteridophyta in the Matalawa National Park is classified as moderate with a value (Ä¤) = 2.76. The diversity of Pteridophyta at the 4 research stations was also included in the medium category with a value (Ä¤) of 2.34 for station I, 2.02 for station II, 2.05 for station III and 2.23 for station IV.